Формите на генитив сингулар во микенскиот грчки и ајолските дијалекти - Џукеска, Елена (Филозофски факултет, Скопје, 2014)
The question of the genitive singular in the Indo-European languages and in particular in the Greek language has been subject of discussion for decades. The data vary in all language families regarding both the form and the syntactical value of the ending. The Greek language occupies a particular place because what is seen as a variety on the level of different Indo-European families within the Greek language is also seen on the level of different dialects. Furthermore what is seen as a variety on the level of different dialects is seen as a variety both on the level of the Aeolic group of dialects and on the level of one single dialect, that is, the Thessalian. The evidence of the tablets written in Linear B constantly throws new light on the old questions: Was the ending *-es/-os/-s in Greek used only as *-os or also as *-es and *-s? Does this ending have just genitive or also an ablative function? How are we to explain the masculine a-stems forms in -ᾱο as regards the ending? Is just the pronominal ending *-syo present in the o/e-stems or also *-so? These issues have been addressed in many important articles. The research conducted in this work is based on the historical-comparative analysis of the genitive forms (in the light of the questions mentioned above) at two time and space points: the Mycenaean tablets from 14 and 12 century B.C. and the Aeolic inscriptions from 8 - 2 century B.C. The examples were compared from phonological, morphological and syntactical aspect in order to clarify the picture of the development of the genitive singular within the Greek language as far as possible and to better understand the parallel use of the different genitive singular endings.
The genitive singular forms in Mycenaean Greek and in the Aeolic Dialects
Keywords: Genitive singular endings, Mycenaean, Aeolic